PENINGKATAN HASIL BELAJAR DENGAN PENERAPAN MODEL PEMBELAJARAN KONSTRUKTIVISME BERBASIS MEDIA PERAGA PADA MATERI ELEKTROPNEUMATIK DALAM MATA KULIAH PNEUMATIK HIDROLIK - Zamroni, Muhammad Rifqi (Journal of Mechanical Engineering Learning, 2014)
This study aims to determine whether there is an increase in student learning outcomes between the use of expository learning model with the model of constructivism. This study uses a quasi-experimental study with a type of pattern pretest-posttest control group design. The study population was 2013 semester of the academic year students who took the 5-Hydraulic Pneumatic course consisting of 2 classes with a number of 90 students. The samples were taken with a saturated sampling method, one class as control group numbering 40 students and one class as experimental group numbering 40 students,. The control group will be given expository teaching model, while the experimental group was given a model of constructivism. Based on the research results obtained, that the average competence elektropneumatik learning outcomes in the control group increased to 58.64 originally 77.41. In the experimental group the average results of the original study increased to 87.21 58.15.